Increased Liveliness of Trunk Muscle Responses in Elite Kayakers and Canoeists - Andrej Kocjan; Nejc Šarabon (MDPI AG, 2020)
Trunk stability functions play an important role in sport and everyday movements. The aim of this study was to analyze trunk strength, trunk muscles onset of activity, and rate of electromyographic rise (RER) in the case of self-inflicted and unexpected trunk loading. Thirty-two healthy young adults (16 elite kayakers/canoeists and 16 non-athletes) were measured with a multi-purpose diagnostic machine. Trunk strength was assessed in standing position. Trunk muscles onset of activity and RER were assessed through unexpected loading over the hands and rapid shoulder flexion, respectively. In comparison with non-athletes, kayakers/canoeists did not significantly differ in trunk strength and showed lower trunk extension/flexion strength ratio (p = 0.008). In general, trunk muscles onset of activity did not significantly differ between the groups. On the contrary, kayakers/canoeists showed higher RER mean values in all the observed muscles (p < 0.041), except in multifidus muscle during self-inflicted movements. Similarly, higher RER variability was observed in the majority of the observed muscles among kayakers/canoeists. Higher RER among kayakers/canoeists could represent a protective mechanism that ensures spine stability and prevents low back pain.